Design and fabrication of asymmetric Mach-Zehnder interferometers based on EpoClad and EpoCore strip waveguides - Magalhães Tiago E.C.; Borme Jérôme; Douglas Temple; Maibohm Christian; Nieder Jana B. (EPJ Web of Conferences, 2024)
Integrated polymeric optical interferometers offer the possibility of developing sensors with low cost, scalability, and easy integration. Although they are not yet competitive with inorganic materials in terms of sensitivity, they have good biocompatibility in general, and suitable designs may provide sufficient sensitivity for biosensing. A new design for integrated Mach-Zehnder interferometers based on asymmetric arms with different widths has been proposed and experimentally demonstrated, avoiding the need for additional fabrication steps for an interaction window where biosamples are placed. The basic sensory principle is built upon the non-zero variation in the difference of the effective refractive index between the two arms due to their different dimensions, causing a phase variation in the output signal. In this work, we present a design optimization method and fabrication results by e-beam lithography for integrated asymmetric Mach-Zehnder interferometers based on strip waveguides made from EpoClad and EpoCore polymers. The operation wavelength was set to 650 nm. The optimization algorithm is based on open-source mode-solver simulations that return the optimal fabrication dimensions of the interferometer, avoiding high-order modes and enhancing single-mode confinement.